Global, regional, and national burdens of pancreatitis in children and adolescents aged 0–24 years from 1992 to 2021: a trend analysis based on the global burden of disease study 2021 - Deng, Ying-han; Qiu, Huabin; Huang, Kangming; Huang, Yanbin; Lian, Fuming; Chen, Yun; Chen, Hongbin (Frontiers in Public Health, 2025)
BackgroundThe younger onset of pancreatitis presents a significant public health challenge. This study aims to analyze the global burden of pancreatitis in younger populations based on the Global Burden of Disease 2021.MethodsThis study uses incidence rates and Disability-Adjusted Life Years (DALYs) to assess the burden of pancreatitis. Joinpoint modeling was used to assess the trend of the burden. Age-Period-Cohort (APC) modeling was used to assess the annual percentage changes by age, as well as the period and cohort relative risks. Norpred modeling was used to predict the burden through 2040.ResultsIn 2021, the global incidence of pancreatitis among younger individuals was 9.16/100,000 (95% UI 5.74–13.85), with an annual average percentage change (AAPC) of 0.13 (95% CI 0.12–0.14). The DALYs was 6.36/100,000 (95% UI 5.21–7.97), with an AAPC of −0.93 (95% CI -1.01 to −0.85). Global incidence rates of pancreatitis have notably increased since 1999, while the overall burden of DALYs has decreased over the past 30 years. In the APC model, different age groups experienced varying risks. According to the Norpred predictive model, by 2040, the global incidence of pancreatitis among younger individuals is projected to reach 313,567 cases, with an incidence rate of 9.07/100,000.ConclusionGlobally, the incidence of pancreatitis in younger individuals has increased over the past three decades. Urgent policy interventions are needed to address healthcare inequities and alleviate this burden.